Sandwich-structured composite material and preparation method thereof

In the preparation of copper/molybdenum copper/copper (CPC) layered composite materials, a sandwich structure layered composite material preparation method and a specially designed infiltration composite graphite jig are used to complete the core material and interface composite in one infiltration. It solves the problems of poor inter-layer bonding force and complex composite process, achieves material preparation with straight interface and good bonding force, and improves production efficiency.

CN119328134APending Publication Date: 2025-01-21CHANGSHA SHENGHUA MICROELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449530.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the preparation process of existing copper/molybdenum copper/copper (CPC) layered composite materials, the bonding force between layers is poor and easy to delaminate. The composite process requires high requirements for the surface roughness of the core material, and it is impossible to improve the bonding force between layers and Reduce intermediate processes and affect production efficiency.

Method used

A sandwich structure layered composite material preparation method is adopted, and a specially designed infiltration composite graphite jig is introduced to complete the core material and interface composite processes in one infiltration, simplifying the process and improving the interlayer bonding force.

Benefits of technology

A sandwich structure composite material with a straight interface and good bonding force is realized, which reduces the smoothing treatment of surface copper, shortens the production cycle, and improves the overall production yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328134A_ABST
    Figure CN119328134A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite material preparation, and discloses a sandwich-structured composite material and a preparation method thereof. The method comprises the following steps: (1) carrying out glue mixing treatment on metal powder; (2) carrying out compression molding treatment on the powder obtained in the step (1) to obtain a green body; (3) degumming and pre-sintering the green body to obtain an intermediate I; (4) placing the intermediate I and an oxygen-free copper plate in a graphite jig, and transferring the graphite jig to pressure infiltration equipment for infiltration treatment to obtain an intermediate II; (5) rolling the intermediate II to obtain an intermediate III; and (6) the intermediate III is sequentially subjected to cutting, linear cutting and grinding treatment, and the composite material with the structure of the first Cu layer, the XCu layer and the second Cu layer is obtained. And X is Mo or W. According to the method provided by the invention, the two processes of core material and interface compounding can be completed through one-time infiltration, the interlayer flatness problem is reduced, the process is simplified, and the overall production yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, and in particular to a sandwich structure composite material and a preparation method thereof. Background Art

[0002] Layered composite materials such as copper / molybdenum copper / copper (CPC) combine the low expansion of molybdenum copper and the high thermal conductivity of copper. They also have high electrical conductivity and thermal conductivity and low thermal expansion coefficient, good density, and are often used as heat sinks, carriers and other components for chip heat dissipation. They are widely used in the field of electronic packaging materials. Such materials generally require planar layered composites with 3 to 5 layers. For example, the outer layer of CMC material is a copper layer with strong conductivity and the middle is a molybdenum layer (core material) with low expansion coefficient. At present, all preparations of CPC require the preparation of core materials first and then use hot pressing or rolling composite methods to obtain a planar layered composite structure. The composite process has high requirements for the surface roughness of the core material, and the interlayer bonding strength of the obtained materials is relatively poor, and it is easy to delaminate. Another method is to obtain a Cu-MoCu-Cu three-layer composite plate by placing copper plates on the upper and lower sides after pre-sintering molybdenum. The three-layer structure is obtained by melt infiltration sintering, which can improve the interlayer bonding strength. During the melt infiltration process, the molybdenum billet skeleton has no support after the copper is liquefied. The melt infiltration process is in a random state and the flatness between the upper, middle and lower three layers cannot be guaranteed. Therefore, there is an urgent need to simultaneously improve the interlayer bonding strength and reduce the number of intermediate processes to improve efficiency.

[0003] The existing technical solutions include two methods: first obtaining the core material and then compounding and melt infiltration compounding. Among them, the method of first obtaining the core material and then compounding includes hot pressing compounding and hot rolling compounding.

[0004] The main difference between hot-rolled composite and hot-pressed composite lies in the different methods of combining the core material and the copper material. Hot-rolled composite is to use a hot rolling mill to hot-roll the plate after the copper material and the core material are alternately stacked, so that the plate is tightly combined under high temperature and high pressure. During the hot rolling process, parameters such as temperature and pressure need to be strictly controlled to ensure the performance of the material. The interface between copper and molybdenum copper is wavy and difficult to ensure straightness and clarity. Problems such as plate deformation or cracking may occur during the rolling process, and corresponding measures need to be taken to prevent and deal with them. The melt infiltration composite method is to place copper plates on both sides of the molybdenum billet skeleton, and obtain a three-layer composite plate after melt infiltration. This method can reduce the composite steps and provide better interlayer bonding. The disadvantage is that the surface of each melt-infiltrated composite plate needs to be flattened, and the thickness ratio and flatness between the three layers cannot be guaranteed, and large-scale stable production cannot be achieved.

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a new preparation method for a sandwich-structured layered composite material. By introducing a specially designed melt-infiltration composite graphite jig, the two processes of core material and interface composite can be completed by melt-infiltration at one time, thereby reducing the defects caused by interlayer flatness problems, reducing the flatness treatment of the surface copper, shortening the production cycle, and having a straight interface with good bonding strength, simplifying the process and improving the overall production yield. Summary of the invention

[0006] The purpose of the present invention is to provide a sandwich structure composite material and a preparation method thereof based on the above technical problem.

[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a sandwich structure composite material, the method comprising the following steps:

[0008] (1) Adding glue to metal powder;

[0009] (2) subjecting the powder obtained in step (1) to compression molding to obtain a green body;

[0010] (3) performing degumming and pre-sintering treatment on the green body to obtain an intermediate I;

[0011] (4) placing the intermediate I, oxygen-free copper plate I, and oxygen-free copper plate II in a graphite jig, and then transferring them to a pressure infiltration device for infiltration treatment to obtain an intermediate II;

[0012] (5) rolling the intermediate II to obtain an intermediate III;

[0013] (6) Cutting, wire cutting, and grinding the intermediate III in sequence to obtain a composite material having a structure of a first Cu layer-XCu layer-a second Cu layer; wherein X is Mo or W;

[0014] The graphite jig is made of graphite and alumina, and the graphite jig includes two identical U-shaped components; the height of the U-shaped component is 20-40 mm, the inner width is 50-60 mm, and the outer width is 60-80 mm, and an inner groove for fixing the intermediate I is provided on the inner side of the U-shaped component, the width of the inner groove is 50-70 mm, the height is 1-5 mm, and the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 2-6 mm.

[0015] Preferably, in step (1), the particle size of the metal powder is 0.5 to 25 um.

[0016] Further preferably, in step (1), the metal powder is molybdenum powder or tungsten powder.

[0017] Preferably, in step (1), the rubber-doping treatment comprises: adding a molding agent to the powder, stirring evenly, baking at 120° C. for 1 to 4 hours, and naturally cooling to room temperature; the molding agent is selected from rubber, stearic acid, paraffin, SBS, PEG or PVA.

[0018] According to a preferred specific embodiment, in step (2), the compression molding process includes: placing the powder obtained in step (1) in a mold with a length of 60 mm and a width of 80 mm, and performing a two-way compression molding process to obtain a square-shaped blank with a relative volume fraction of metal powder of 0.3 to 0.8.

[0019] Preferably, in step (3), the degumming pre-burning treatment is carried out under reducing atmosphere or vacuum, and when the temperature reaches 1000° C., the furnace is naturally cooled to room temperature.

[0020] Further preferably, in step (4), the conditions of the infiltration treatment meet the following requirements: a heating rate of 3 to 20°C / min, a temperature of 1400°C, and keeping at 1400°C for 4 hours.

[0021] Preferably, in step (4), in the U-shaped component of the graphite fixture, the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 2 to 5.7 mm, and the height of the inner groove is 2 to 4 mm.

[0022] Preferably, in step (5), the rolling treatment is performed on the intermediate II at room temperature using two cross cold rolling processes in perpendicular directions.

[0023] Preferably, in step (6), the trimming process is to trim off the cracked or thin corners around the intermediate III, and cut them into the same size, and then perform wire cutting and double-sided grinding to make the surface smooth.

[0024] The second aspect of the present invention provides a sandwich structure composite material prepared by the method described in the first aspect of the present invention.

[0025] Preferably, in the composite material, the thickness ratio of the first Cu layer, the XCu layer and the second Cu layer is 1:1 to 5:1.

[0026] The method provided by the present invention also has at least the following beneficial effects:

[0027] (1) The method provided by the present invention can complete the two processes of core material and interface composite infiltration at one time, reduce the problem of interlayer flatness, reduce the flatness treatment of surface copper, shorten the production cycle, and its interface is flat and has good bonding strength, which simplifies the process and improves the overall production yield.

[0028] (2) The method provided by the present invention is simple, low-cost and high-yield, and has little pollution to the environment and a relatively large market capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a cross-sectional view of the sandwich structure composite material obtained in Example 2 of the present invention;

[0030] Figure 2 Schematic diagram of the placement of the intermediate I and the oxygen-free copper plate in the graphite jig in step (4) of the embodiment of the present invention;

[0031] Figure 3 is a cross-sectional view of the intermediate I and the oxygen-free copper plate placed in a graphite jig in step (4) of an embodiment of the present invention;

[0032] Figure 4 is a cross-sectional view of the intermediate II obtained in the embodiment of the present invention;

[0033] Figure 5 It is a cross-sectional view of intermediate II-a, intermediate II-b, and intermediate II-c obtained by rolling in comparative example 2;

[0034] Figure 6 is a schematic diagram of a U-shaped component in a graphite jig used in step (4) of Example 1 of the present invention;

[0035] Figure 7 It is a cross-sectional view of the U-shaped component in the graphite fixture used in step (4) of Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] In the present invention, in the obtained composite material, the thickness ratio of the first Cu layer, the XCu layer, and the second Cu layer is not limited to 1:1 to 5:1, wherein the thickness ratio of the XCu layer can be adjusted as needed, but the thickness of the first Cu layer and the second Cu layer must be the same.

[0038] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0039] In the following examples, unless otherwise specified, the particle size of the molybdenum powder is 0.5-25 um, the particle size of the tungsten powder is 0.5-20 um, and the relative molecular weight of PEG is 400-3000.

[0040] In the following examples, unless otherwise specified, in the graphite fixture I, the height of the U-shaped component is 30 mm, the inner width is 55 mm, the outer width is 70 mm, the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 5.7 mm, the height of the inner groove is 4 mm, and the width of the inner groove is 60 mm;

[0041] In the graphite fixture II, the height of the U-shaped component is 30 mm, the inner width is 55 mm, the outer width is 70 mm, the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 4.5 mm, the height of the inner groove is 3 mm, and the width of the inner groove is 60 mm;

[0042] In the graphite fixture III, the height of the U-shaped component is 30 mm, the inner width is 55 mm, the outer width is 70 mm, the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 2 mm, the height of the inner groove is 2 mm, and the width of the inner groove is 60 mm.

[0043] In the following examples, unless otherwise specified, the specifications of oxygen-free copper plate I-1 are: 70 mm in length, 50 mm in width, 4.3 mm in thickness, and 172 g in weight;

[0044] Oxygen-free copper plate I-2 specifications: length 70mm, width 50mm, thickness 4.3mm, weight 134g;

[0045] Specifications of oxygen-free copper plate I-3: length 70mm, width 50mm, thickness 1.9mm, weight 59.5g.

[0046] Example 1

[0047] This example is used to provide a combination Figure 2 and Figure 3 A method for preparing a sandwich structure composite material, the method comprising the following steps:

[0048] (1) Rubber-doped powder: 5000 g of molybdenum powder was added with 100 g of rubber, stirred evenly, and dried at 120° C. for 4 h, and cooled naturally to room temperature to obtain rubber-doped molybdenum powder.

[0049] (2) Compression molding: The molybdenum powder of step (1) was placed in a mold with a length and width of 60 mm and 80 mm, respectively, with a weight of 126 g, and subjected to bidirectional compression molding to obtain a molybdenum blank with a thickness of 4 mm.

[0050] (3) Debinding and pre-sintering: The molybdenum blank is spread flat in a graphite boat, and then transferred to a degreasing furnace for thermal degreasing in a hydrogen atmosphere. When the temperature reaches 1000° C., it is naturally cooled to room temperature along with the furnace to obtain intermediate I.

[0051] (4) Infiltration: The intermediate I, oxygen-free copper plate I-1, and oxygen-free copper plate II-1 are placed in a graphite jig I, and then transferred to a pressure infiltration device for infiltration treatment, and naturally cooled to room temperature with the device to obtain an intermediate II; the conditions of the infiltration treatment meet the following requirements: a heating rate of 3 to 20°C / min, a temperature of 1400°C, and keeping at 1400°C for 4 hours.

[0052] (5) Rolling: In a hydrogen atmosphere, the intermediate II is heated to 850°C, transferred to a rolling mill for rolling, and repeatedly heated at 850°C and rolled repeatedly to obtain an intermediate III with a thickness of less than 3 mm; the rolling is carried out at room temperature, according to the required thickness (2 mm) and interlayer ratio (1:1:1), using two cross cold rolling processes in perpendicular directions.

[0053] (6) Cutting, wire cutting and grinding: first, the cracked or thin corners around the intermediate III are cut off, and the intermediate III is cut into the same size, and then wire cutting is performed to obtain the required outer dimensions, and double-sided grinding is performed using a grinding device to make the surface flat, thereby obtaining a composite material with a thickness of 2 mm and a structure of a first Cu layer-MoCu layer-second Cu layer; in the composite material, the thickness of the first Cu layer, the MoCu layer, and the second Cu layer is 1:1:1.

[0054] Example 2

[0055] This example is used to provide a combination Figure 2 and Figure 3 A method for preparing a sandwich structure composite material, the method comprising the following steps:

[0056] (1) Glue-doping the powder: Take 5000g of molybdenum powder, add 100g of PEG with a molecular weight of 1000, stir evenly, bake at 120°C for 4h, and cool naturally to room temperature to obtain glue-doped molybdenum powder.

[0057] (2) Compression molding: The rubber-doped molybdenum powder weighing 94.5 g was placed in a mold with a length and width of 60 mm and 80 mm, respectively, and subjected to bidirectional compression molding to obtain a molybdenum blank with a thickness of 3 mm.

[0058] (3) Debinding and pre-sintering: The molybdenum blank is spread flat in a graphite boat, and then transferred to a degreasing furnace for thermal degreasing in a hydrogen atmosphere. When the temperature reaches 1000° C., it is naturally cooled to room temperature along with the furnace to obtain intermediate I.

[0059] (4) Infiltration: According to Figure 2 and Figure 3 As shown, the intermediate I, oxygen-free copper plate I-2, and oxygen-free copper plate II-2 are placed in a graphite fixture II, and then transferred to a pressure infiltration device for infiltration treatment, and naturally cooled to room temperature with the equipment to obtain an intermediate II; the conditions of the infiltration treatment meet the following conditions: a heating rate of 3 to 20°C / min, a temperature of 1400°C, and keeping at 1400°C for 4 hours.

[0060] (5) Rolling: In a hydrogen atmosphere, the intermediate II is heated to 850°C, transferred to a rolling mill for rolling, and repeatedly heated at 850°C, and rolled repeatedly to obtain an intermediate III with a thickness of less than 3 mm; the rolling is carried out at room temperature, according to the required thickness (2 mm) and interlayer ratio (1:1:1), using two perpendicular cross cold rolling.

[0061] (6) Cutting, wire cutting and grinding: first, the cracked or thin corners around the intermediate III are cut off, and the intermediate III is cut into the same size, and then wire cutting is performed to obtain the required outer dimensions, and double-sided grinding is performed using a grinding device to make the surface flat, thereby obtaining a composite material with a thickness of 2 mm and a structure of a first Cu layer-MoCu layer-second Cu layer; in the composite material, the thickness of the first Cu layer, the MoCu layer, and the second Cu layer is 1:1:1.

[0062] Example 3

[0063] In this example, a sandwich structure composite material is prepared according to the method of Example 1, except that in step (1), the same mass of tungsten powder is taken; in step (2), the glue-doped tungsten powder is placed in the mold with a weight of 108 g and subjected to bidirectional compression molding to obtain a tungsten blank with a thickness of 2 mm; in step (4), the intermediate I, oxygen-free copper plate I-3, and oxygen-free copper plate II-3 are placed in a graphite fixture III, and the remaining steps and parameters are the same as in Example 1.

[0064] Among them, a composite material with a thickness of 2 mm and a structure of a first Cu layer-WCu layer-second Cu layer is obtained; in the composite material, the thickness of the first Cu layer, the WCu layer, and the second Cu layer is 1:2:1.

[0065] Comparative Example 1

[0066] This example adopts a method for preparing a sandwich structure composite material by hot pressing composite method, and the method includes:

[0067] (1) Compression molding: 5000 g of molybdenum powder was taken and subjected to bidirectional compression molding in a mold with a length and width of 60×80 mm according to a weight of 252 g to obtain a molybdenum blank with a thickness of 8 mm.

[0068] (2) Debinding and pre-sintering: The molybdenum blank is laid flat in a graphite boat, and then transferred to a degreasing furnace for hot degreasing. When the temperature reaches 1000° C., it is naturally cooled to room temperature along with the furnace to obtain intermediate I.

[0069] (3) Infiltration: The intermediate I and the oxygen-free copper plate are placed in an atmosphere infiltration device for infiltration treatment, and the temperature is raised to 1400° C. according to a heating curve. The temperature is naturally cooled to room temperature along with the device, and the obtained molybdenum-copper billet is surface treated to obtain a molybdenum-copper core material with a smooth surface and a size of 80×60×7.8 mm.

[0070] (4) Rolling: Take two copper plates with a size of 80×60×10 mm, clamp the molybdenum-copper core material between the two copper plates, and place them at the center of the lower die of the hot pressing furnace. Start the hot pressing sintering furnace, press the upper die downward on the copper plate to form a pressure of 15 MPa, heat to 850°C in a hydrogen atmosphere, keep the temperature and pressure for 30 minutes, keep the pressure constant, and cool with the furnace to obtain a composite ingot with a molybdenum-copper alloy as the middle layer and a copper layer with a thickness of 17.5 mm on both sides. Under the protection of the atmosphere, heat the composite ingot to 800°C and keep the temperature for 20 minutes, and hot roll it to a thickness of 3 mm.

[0071] (5) Post-treatment: The cracked or thin corners of the material obtained in step (4) are cut off, and the material is cut into small squares of the same size, washed with dilute sulfuric acid to remove the oxide scale, and then cold-rolled to a thickness of 2 mm, and then surface-grinded to make the surface smoother to obtain a Cu-MuCu-Cu composite material having a structure of Cu layer I-MuCu layer-Cu layer II, wherein the thickness ratio of Cu layer I, MuCu layer, and Cu layer II is 1:1:1.

[0072] Comparative Example 2

[0073] This example adopts a method for preparing a sandwich structure composite material by melt infiltration composite method, and the method includes:

[0074] (1) Compression molding: 5000 g of molybdenum powder was taken and subjected to bidirectional compression molding in a mold with a length and width of 60×80 mm according to a weight of 252 g to obtain a molybdenum blank with a thickness of 8 mm.

[0075] (2) Debinding and pre-sintering: The molybdenum blank is laid flat in a graphite boat, and then transferred to a degreasing furnace for hot degreasing. When the temperature reaches 1000° C., it is naturally cooled to room temperature along with the furnace to obtain intermediate I.

[0076] (3) Infiltration: The intermediate I is placed between two copper plates with a thickness of 20 mm each, and placed in a hydrogen atmosphere furnace for infiltration treatment. When the temperature reaches 1400° C., the infiltration is carried out at this temperature for 3 hours, and the equipment is naturally cooled to room temperature to obtain an intermediate II completely coated with copper.

[0077] (4) Rolling: Cut along the center line of the intermediate II to obtain Figure 5 The intermediates II-a, II-b and II-c of the structure shown are selected such that the surface copper layer thickness of the intermediate II does not differ by more than 4 mm, are kept at 800°C for 20 minutes, and are hot-rolled multiple times to a thickness of 3 mm.

[0078] (5) Post-treatment: The material obtained in step (4) is cleaned with dilute sulfuric acid to remove the oxide scale, and then cold-rolled to a thickness of 2 mm for multiple times, and then surface-polished to make the surface smoother, thereby obtaining a Cu-MuCu-Cu composite material having a structure of Cu layer I-MuCu layer-Cu layer II, wherein the thickness ratio of Cu layer I, MuCu layer, and Cu layer II is 1:1:1.

[0079] Test Case

[0080] The materials obtained in the above examples and comparative examples were tested, and the results are shown in Table 1.

[0081] The shear strength was measured with reference to GB6396-1995, and the obtained sandwich structure plate was processed into a shear tensile specimen 1. The copper-molybdenum-copper-copper composite plate obtained in the embodiment of the present invention was annealed and processed into a shear tensile specimen. The detection instrument used was an Instron 8042 electronic universal tensile testing machine, the tensile speed was 2 mm / min, the total thickness of the specimen was 2 mm, and the width of the specimen was 5 mm.

[0082] The thickest and thinnest sizes of the side core material of a composite material with a thickness of 2 mm and an interlayer ratio of 1:1:1 were measured by a profilometer, and the ratio of the extreme core material thickness obtained by different preparation methods to the total thickness of the sample was calculated to measure the flatness of the interlayer interface of the sample; the calculation formula is: interlayer interface flatness = [total sample thickness - (maximum core material thickness - minimum core material thickness)] / total sample thickness × 100%;

[0083] The thickness of the copper layer on both sides was confirmed by a profilometer. The thickness ratio was the ratio of one side as the reference to the average thickness of the other side. The parallelism between the two planes and the core layer was confirmed by connecting multiple points into a line. Figure 5 Due to various abnormal conditions, it is impossible to continue rolling to obtain finished products with corresponding thickness ratio, and the overall yield rate is less than 30%.

[0084] Table 1

[0085] serial number Interface bonding strength / (MPa) Straightness of interlayer interface / % Copper layer thickness ratio on both sides Example 1 120 97.5 1:1 Example 2 125 98.3 1:1 Example 3 140 98.5 1:1 Comparative Example 1 80 94 1:0.95 Comparative Example 2 120 97.5 1:0.7

[0086] It can be seen from the results in Table 1 that the composite material prepared by the method of the present invention has a significantly better sandwich structure, and the composite material has better upper and lower copper layer surfaces, and it is easier to ensure that the thickness of the copper layers on both sides is consistent. The method of the present invention can improve the yield and efficiency of the product.

[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a sandwich structure composite material, characterized in that: The method comprises the following steps: (1) Adding glue to metal powder; (2) subjecting the powder obtained in step (1) to compression molding to obtain a green body; (3) performing degumming and pre-sintering treatment on the green body to obtain an intermediate I; (4) placing the intermediate I, oxygen-free copper plate I, and oxygen-free copper plate II in a graphite jig, and then transferring them to a pressure infiltration device for infiltration treatment to obtain an intermediate II; (5) rolling the intermediate II to obtain an intermediate III; (6) Cutting, wire cutting, and grinding the intermediate III in sequence to obtain a composite material having a structure of a first Cu layer-XCu layer-a second Cu layer; wherein X is Mo or W; The graphite jig is made of graphite and alumina, and the graphite jig includes two identical U-shaped components; the height of the U-shaped component is 20-40 mm, the inner width is 50-60 mm, and the outer width is 60-80 mm, and an inner groove for fixing the intermediate I is provided on the inner side of the U-shaped component, the width of the inner groove is 50-70 mm, the height is 1-5 mm, and the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 2-6 mm.

2. The method according to claim 1, wherein: In step (1), the particle size of the metal powder is 0.5 to 25 μm; And / or, in step (1), the metal powder is molybdenum powder or tungsten powder.

3. The method according to claim 1 or 2, wherein: In step (1), the glue-doping treatment includes: adding a molding agent to the powder, stirring evenly, baking at 120° C. for 1 to 4 hours, and naturally cooling to room temperature; the molding agent is selected from rubber, stearic acid, paraffin, SBS, PEG or PVA.

4. The method according to claim 1 or 2, wherein: In step (2), the compression molding process comprises: placing the powder obtained in step (1) in a mold having a length of 60 mm and a width of 80 mm, and performing a bidirectional compression molding process to obtain a block-shaped blank having a relative volume fraction of metal powder of 0.3 to 0.8; And / or, in step (3), the degumming pre-burning treatment is carried out under reducing atmosphere or vacuum, and when the temperature reaches 1000° C., the degumming pre-burning treatment is naturally cooled to room temperature in the furnace.

5. The method according to claim 1 or 2, wherein: In step (4), the conditions of the infiltration treatment are as follows: a heating rate of 3 to 20°C / min, a temperature of 1400°C, and keeping at 1400°C for 4 hours.

6. The method according to claim 1 or 2, wherein: In step (4), in the U-shaped component of the graphite fixture, the distance d between the bottom edge of the inner groove and the inner bottom edge of the U-shaped component is 2 to 5.7 mm, and the height of the inner groove is 2 to 4 mm.

7. The method according to claim 1 or 2, wherein: In step (5), the rolling treatment is performed on the intermediate II at room temperature by using two cross cold rolling processes in perpendicular directions.

8. The method according to claim 1 or 2, wherein: In step (6), the trimming process is to trim off the cracked or thin corners around the intermediate III, and cut them into the same size, and then perform wire cutting and double-sided grinding to make the surface smooth.

9. A sandwich structure composite material prepared by the method according to any one of claims 1 to 8.

10. The sandwich structure composite material according to claim 9, wherein: In the composite material, the thickness ratio of the first Cu layer, the XCu layer, and the second Cu layer is 1:1 to 5:1.